Can anticipatory supply chain decision making manage the pandemic's effect? A regime switching game. Issue 10 (2022) - Mukherjee, Arka; Ganguly, Anirban; Kumar, Chitresh; Chowdhury, Priyabrata
Abstract: The COVID-19 pandemic has shown that stock outs of essential items like hand sanitizers, tissue papers and other items of hygiene and daily use have been characteristic of a supply chain, especially immediately following a pandemic wave. Consequently, retailers have to indulge in substantial supplier management efforts to ensure product availability during a pandemic wave. Using a piecewise deterministic differential game, we model a scenario where, while anticipating a pandemic wave, a supplier decides on product availability efforts to ensure product availability under the impending threat of stock outs. A market leader coordinating retailer, on the other hand, decides on the proportion of the costs of the efforts to be shared with the supplier.